Retracted: Internet of Things Technology in Monitoring System of Sustainable Use of Soil and Land Resources - Zhaoya Chen; Daobo Wang; Lijun Ma; Yaheng Chen (IEEE Access)
With the development of global economy, the sustainable use of land resources has become a key research topic in the current social and economic development. To do a good job in the sustainable use of land resources can solve such problems as waste of land resources, quality degradation, environmental damage, ecological imbalance and so on. How to realize the sustainable utilization of resources, the first thing to be solved is the sustainable monitoring of land resources. At present, many researches have been done in this field at home and abroad, but in conclusion, there are some problems, that is, the basic theory is not deep and the practical application is less. Therefore, this paper will study the application of the monitoring system of the sustainable use of soil and land resources under the support of the Internet of things big data technology, and establish a practical monitoring system of the sustainable use of land resources. The monitoring system in this paper makes full use of modern science and technology. On the basis of intelligent technology, combined with the actual situation of land resources in China, according to the practical problems, the construction principles of evaluation index system and index construction are established. In the aspect of monitoring system construction, we have greatly optimized the traditional construction method, which makes the system in this paper have better adaptability, scalability and accuracy. In order to further verify the reliability of the system, this paper carries out the performance test, accuracy test, and monitoring test in extremely harsh environment. Finally, the data show that the system can be applied to most of the land environment to monitor the sustainability of land resources.